Botanical Contributions of Nepalese Scientists to Climate Change in Nepal: A Review (Patan Pragya, 2024)
Climate Change has been a recent consequence of global warming among other detrimental anthropogenic activities. It concerns studies among various disciplines of social and natural science. The objective of this paper is to document the studies on Climate Change by Nepalese Scientists in field of Botany. Research and review papers on climate change studies in various fields of Botany were acquired from Google Scholar. Altogether 32 papers/studies were obtained till 2024. They are from different fields of Botany such as forestry, agriculture, ethnobotany, environment, biological invasion, dendrochronology, tree line shift, food and water security, disaster risks, etc. The data collected were analyzed to present them conveniently to the general readers. There was a short review of the discourses from the contributor Botanists from Nepal. There was 31% study during 2010-2015, 47% during 2015-2020 and 22% during 2020-2024. This study will be fruitful for finding who is who in Botany and finding the gaps in climate change studies from Nepal with perspectives of plant science.